Analisis Pengaruh Mendengarkan Musik Terhadap Tingkat Fokus dan Produktivitas Mahasiswa dalam Mengerjakan Tugas - KHARISMA, FEBBY FERIYANI; Marlina; Wilda Yulia Rusyida (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Being a student is a challenge in itself for every individual who goes through it. The reason why listening to music affects a person's mood is because listening to music itself is a big stimulus for the brain. The large number of task demands is a stress that can cause stress for students. One therapy used to deal with stress is listening to music. It turns out that listening to music can not only relieve stress, for some students listening to music at a low tempo can also increase focus in doing assignments. The purpose of this literature is to find out how music influences students' focus in doing assignments. The method used is the literature observation method. Library review is a literature search and research by reading various journals related to research.